The transformation of political community : ethical foundations of the Post-Westphalian era - Linklater, Andrew (Cambridge, UK : Polity Press, 2004)
Anarchy, community and critical international theory. The critique of neo-realism. The problem of community in international relations. The changing context of the modern state. Theorising the reconfiguration of political community -- Universality, differ
Includes bibliographical references (p.[241]-256) and index.
Keywords: Citizenship; International relations -- Social aspects; Community -- Political aspects; Uluslararası ilişkiler -- Sosyal yönler; Topluluk -- Siyasal yönler; Vatandaşlık